Eco-friendly PVC resin composition with high durability and microplastic reduction and PVC pipe using the same

KR103017774B1Active Publication Date: 2026-09-16NEW VOTECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250184847
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-09-16
Estimated Expiration
2045-11-28
Patent Text Reader

Abstract

The present invention relates to an eco-friendly PVC resin composition and pipes that structurally suppress surface peeling and cracking, which are causes of microplastic generation, by introducing surface-modified nano calcium carbonate (Nano-CaCO3) and an adsorption system to dramatically improve the impact resistance and wear resistance of the pipes. To this end, the invention provides a PVC resin composition comprising a PVC resin, an impact modifier, a filler, a lubricant, a UV blocker, a nonionic surfactant, and a microplastic adsorbent, wherein the filler comprises nano calcium carbonate (Nano-CaCO3) surface-modified with at least one of stearic acid or a silane compound, and the microplastic adsorbent comprises an inorganic adsorbent, a heat stabilizer, water glass, and a water-soluble anionic polysaccharide.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an eco-friendly PVC resin composition and a PVC pipe using the same, and more specifically, to an eco-friendly PVC resin composition and a pipe that structurally suppresses surface peeling and cracking, which are causes of microplastic generation, by introducing surface-modified nano calcium carbonate (Nano-CaCO3) and a special adsorption system to dramatically improve the impact resistance and wear resistance of the pipe. Background Technology

[0002] Generally, PVC pipes are widely used in various fields, such as water and sewage systems, due to their numerous advantages in terms of durability, processability, and cost competitiveness. However, there are issues regarding human and environmental hazards caused by the use of lead-based stabilizers and endocrine disruptor-derived plasticizers, as well as the potential generation of microplastics due to friction or wear on the inner walls of the pipes during long-term use. Accordingly, there is a demand for the development of eco-friendly PVC water and sewage pipes based on environmentally friendly additives that can suppress the generation of microplastics while maintaining existing physical properties. Prior art literature

[0003] Korean Registered Patent Publication No. 10-1564737 (Oct. 30, 2015) Korean Published Patent Publication No. 10-2024-0176949 (Dec. 26, 2024) The problem to be solved

[0004] The present invention provides a PVC resin composition that suppresses surface cracking and peeling, which are the source of microplastic generation, by applying surface-modified nano-CaCO3 to improve the toughness and wear resistance of a PVC matrix, and a PVC pipe manufactured using the same.

[0005] In addition, the present invention provides a PVC resin composition that simultaneously satisfies mechanical properties and eco-friendliness by optimizing a water-soluble anionic polysaccharide and inorganic adsorbent system that helps the dispersibility of nano-fillers and can capture residual microplastics, and a PVC pipe manufactured using the same.

[0006] The technical problems of the present invention are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by a person skilled in the art to which the present invention pertains from the description below. means of solving the problem

[0007] In order to achieve the above-mentioned problem, a PVC resin composition according to an embodiment of the present invention comprises a PVC resin, an impact modifier, a filler, a lubricant, a UV blocker, a nonionic surfactant, and a microplastic adsorbent, wherein the filler comprises nano-calcium carbonate (Nano-CaCO3) surface-modified with at least one of stearic acid or a silane compound, and the microplastic adsorbent may comprise an inorganic adsorbent, a heat stabilizer, water glass, and a water-soluble anionic polysaccharide.

[0008] According to an embodiment of the present invention, with respect to 100 parts by weight of the PVC resin, the composition may include 2 to 15 parts by weight of the impact modifier, 3 to 7 parts by weight of the surface-modified nano calcium carbonate, 0.3 to 1 part by weight of the lubricant, 0.2 to 1 part by weight of the UV blocker, 0.3 to 0.5 parts by weight of the nonionic surfactant, and 0.5 to 10 parts by weight of the microplastic adsorbent.

[0009] According to an embodiment of the present invention, the microplastic adsorbent may comprise, with respect to 100 parts by weight of the PVC resin, 0.2 to 5 parts by weight of an inorganic adsorbent including zeolite, silica, and activated carbon, 1.5 to 6 parts by weight of a heat stabilizer including a Ca-Zn series compound, 0.1 to 1 part by weight of water glass which is sodium hydroxide silicate, and 0.2 to 1.0 parts by weight of the water-soluble anionic polysaccharide.

[0010] According to an embodiment of the present invention, the heat stabilizer may include at least one of a Ca-Zn series heat stabilizer, magnesium aluminum hydroxycarbonate, zinc stearate (Zn-St; ZincStearate), and calcium stearate (Ca-St; Calcium Stearate).

[0011] According to an embodiment of the present invention, the inorganic adsorbent may be configured to include 0.2 to 5 parts by weight of zeolite, 0.2 to 3 parts by weight of silica, and 0.2 to 2 parts by weight of activated carbon powder, based on 100 parts by weight of the PVC resin.

[0012] According to an embodiment of the present invention, the microplastic adsorbent may be configured to further include 0.2 to 1 weight part of water glass with respect to 100 weight parts of PVC resin.

[0013] According to an embodiment of the present invention, the water glass may be sodium hydroxide silicate.

[0014] According to an embodiment of the present invention, the water-soluble anionic polysaccharide comprises 0.5 to 1.0 parts by weight of carboxymethylcellulose (CMC) and 0.1 to 0.5 parts by weight of xanthan gum per 100 parts by weight of the PVC resin, and the polysaccharide can suppress the re-aggregation of nano calcium carbonate and improve dispersion stability.

[0015] According to an embodiment of the present invention, the surface-modified nano calcium carbonate is surface-treated with 0.5 to 2 weight percent of stearic acid relative to the weight of the nano calcium carbonate through a dry coating method, thereby strengthening interfacial adhesion with PVC resin and suppressing particle detachment due to friction.

[0016] According to an embodiment of the present invention, the surface-modified nano calcium carbonate may have an average particle size of 30 to 50 nm. Effects of the invention

[0017] According to the embodiments of the present invention described above, surface-modified nano-CaCO3 can suppress crack deflection and induce cavitation within a PVC matrix, thereby structurally suppressing the generation of microplastics caused by wear and fragmentation.

[0018] In addition, according to the embodiments of the present invention described above, the interfacial bonding force between the nano filler and PVC is strengthened, so that tensile strength, flexural strength, and impact strength can be dramatically improved compared to existing technology.

[0019] In addition, according to the embodiments of the present invention described above, the synergistic effect of the stearic acid / silane modification and the nonionic surfactant / polysaccharide system can prevent re-aggregation of nanoparticles and enable uniform dispersion, thereby improving surface quality.

[0020] In addition, according to the embodiments of the present invention described above, process convenience can be provided by excluding harmful heavy metal stabilizers and using eco-friendly materials, while allowing existing extrusion equipment to be used as is.

[0021] The effects according to the technical concept of the present disclosure are not limited to those mentioned above, and other unmentioned effects will be clearly understood by a person skilled in the art from the description below. Specific details for implementing the invention

[0022] Hereinafter, specific embodiments of the present invention will be described with reference to the drawings. The following detailed description is provided to facilitate a comprehensive understanding of the methods, apparatuses, and / or systems described herein. However, this is merely illustrative and the present invention is not limited thereto.

[0023] In describing the embodiments of the present invention, if it is determined that a detailed description of known technology related to the present invention may unnecessarily obscure the essence of the present invention, such detailed description will be omitted. Furthermore, the terms described below are defined considering their functions in the present invention, and these may vary depending on the intentions or practices of the user or operator. Therefore, such definitions should be based on the content throughout this specification. The terms used in the detailed description are merely for describing the embodiments of the present invention and should not be limiting in any way.

[0024] An eco-friendly PVC resin composition having a function to reduce microplastic generation according to some embodiments of the present invention may be configured to include a PVC resin, an impact modifier, a filler, a lubricant, a UV blocker, a nonionic surfactant, and a microplastic adsorbent. Specifically, the eco-friendly PVC resin composition may be configured to include, with respect to 100 parts by weight of PVC resin, 2 to 15 parts by weight of an impact modifier, 3 to 7 parts by weight of surface-modified nano calcium carbonate as a filler, 0.3 to 1 part by weight of a lubricant, 0.2 to 1 part by weight of a UV blocker, 0.3 to 0.5 parts by weight of a nonionic surfactant, and 0.5 to 10 parts by weight of a microplastic adsorbent.

[0025] PVC resin may be scale chloride resin, but is not limited thereto.

[0026] Impact modifiers are mixed into PVC resin to increase fracture, tensile, compressive, flexural, and impact strength. Impact modifiers may include one or more of acrylic copolymers and CPE (Chloride Polyethylene).

[0027] The lubricant is mixed into the PVC resin to increase the fluidity, extrudability, and moldability of the resin, and to increase thermal stability to prevent thermal decomposition during extrusion molding. Such lubricants may include butyl methacrylate and methyl methacrylate.

[0028] Butyl methacrylate and methyl methacrylate can be mixed in a weight ratio of 1:1 to 1:2, and within this range, there is an advantageous effect in securing excellent extrudability and moldability of the pipe.

[0029] A UV blocker is added to prevent the pipes from deteriorating due to ultraviolet rays. The UV blocker may be composed of a polymer having azo and benzene groups, and for example, the UV blocker may be azodiphenylaniline.

[0030] Nonionic surfactants may be added to aid in emulsification and dispersion and to improve mutual miscibility, and the nonionic surfactants may be, but are not limited to, alcohol ethoxylates (AEO), alkylphenol ethoxylates (APEO), PEG-stearate, PEG-lauryl ether, PEG-oleate, sorbitan ester, polyoxyethylene sorbitan, alkyl polyglucoside (APG), sucrose ester, polyether-modified siloxane, etc.

[0031] In an embodiment of the present invention, the filler may be a surface-modified nano-filler, and may include nano-calcium carbonate (Nano-CaCO3) that is surface-modified with at least one of stearic acid or silane compounds and has an average particle size in the range of 30 to 50 nm.

[0032] In addition, the nano filler can be used in an amount of 1 to 10 parts by weight, preferably 3 to 7 parts by weight, per 100 parts by weight of PVC resin. Here, if it exceeds 7 parts by weight, a decrease in impact strength due to agglomeration may occur.

[0033] In particular, nano calcium carbonate is surface-treated with 0.5 to 2 weight percent of stearic acid relative to the weight of nano calcium carbonate through a dry coating method, which can strengthen interfacial adhesion with PVC resin and suppress particle detachment due to friction.

[0034] By using these nano-sized calcium carbonate particles as a filler, energy dissipation during cavitation and shear deformation is induced, and crack deflection is blocked, thereby preventing micro-delamination on the pipe surface.

[0035] The microplastic adsorbent is a composite for capturing residual or trace amounts of microplastics and harmful substances, and may be included in an amount of 0.5 to 10 parts by weight per 100 parts by weight of PVC resin. In particular, the microplastic adsorbent may be composed of an inorganic adsorbent, a heat stabilizer, water glass, and a water-soluble anionic polysaccharide. Specifically, the microplastic adsorbent may comprise, with respect to 100 parts by weight of the PVC resin, 0.2 to 5 parts by weight of an inorganic adsorbent including zeolite, silica, and activated carbon, 1.5 to 6 parts by weight of a heat stabilizer including a Ca-Zn series compound, 0.1 to 1 part by weight of water glass which is sodium hydroxide silicate, and 0.2 to 1.0 parts by weight of the water-soluble anionic polysaccharide.

[0036] The inorganic adsorbent may comprise 0.2 to 5 parts by weight of zeolite, 0.5 to 3 parts by weight of silica, and 0.2 to 2 parts by weight of activated carbon powder, based on 100 parts by weight of the PVC resin.

[0037] Zeolite, silica, and activated carbon powders can be added to suppress the expression of harmful substances such as microplastics through adsorption capacity, regulate pH, deodorize, provide filling, prevent slippage, and reinforce mechanical properties. When mixed according to the aforementioned composition ratio, adsorption performance can be achieved while minimizing problems such as reduced processability of pipes, deterioration of mechanical properties, and degradation of surface quality.

[0038] Water-soluble anionic polysaccharide agents are natural extracts added to assist in dispersion stabilization, viscosity control, prevention of internal aggregation, and moisture retention, comprising carboxymethylcellulose (CMC), carboxymethylstarch (CMS), xanthan gum, gellan gum, welan gum, diutan gum, rhamsan gum, succinoglycan, carrageenan, alginate, fucoidan, pectin, pectate, gum arabic, hyaluronic acid, chondroitin sulfate, heparin, heparan sulfate, dextran sulfate, and agaropectin. It may include at least one of the following.

[0039] Preferably, the water-soluble anionic polysaccharide agent comprises 0.5 to 1 part by weight of a first polysaccharide selected from carboxymethylcellulose (CMC), carboxymethyl starch (CMS), succinoglycan, alginate, fucoidan, chondroitin sulfate, heparin, heparan sulfate, and dextran sulfate, and 0.5 to 1 part by weight of xanthan gum, gellan gum, welan gum, diutan gum, rhamsan gum, carrageenan, pectin, pectate, gum arabic, hyaluronic acid, and It may include 0.1 to 0.5 parts by weight of a second polysaccharide selected from agaropectin, in which case the aggregation of inorganic adsorbents can be suppressed and interfacial bonding within the PVC matrix can be strengthened, and accordingly, tensile / impact / flexural strength can all be significantly improved.

[0040] In particular, the water-soluble anionic polysaccharide according to the embodiment of the present invention is intended to secondarily inhibit the aggregation of nano-fillers and assist interfacial bonding, and can be used by mixing 0.5 to 1 part by weight of carboxymethylcellulose (CMC) and 0.1 to 0.5 parts by weight of xanthan gum. Such CMC and xanthan gum can improve dispersion stability by forming hydrogen-bonded bridges on the surface of nano-particles.

[0041] In order to replace existing stabilizers for harmful substances such as lead and phthalates and to exhibit thermal stabilization and decomposition inhibition capabilities, the heat stabilizer may be configured to include at least one of a Ca-Zn series heat stabilizer, magnesium aluminum hydroxycarbonate, zinc stearate (Zn-St; Zinc Stearate), and calcium stearate (Ca-St; Calcium Stearate).

[0042] Water glass may be added to increase bonding stability, antibacterial assistance, and heat resistance, and the water glass may refer to an aqueous solution of sodium hydroxide silicate or sodium silicate (Na2SiO3).

[0043] Meanwhile, 2 to 15 parts by weight of an acrylic copolymer or CPE, etc., may be used as an impact modifier.

[0044] The lubricant may be 0.3 to 1 weight part of a mixture of butyl methacrylate and methyl methacrylate, etc.

[0045] Nonionic surfactants can be used in an amount of 0.3 to 0.5 parts by weight of nonionic series such as PEG-stearate and alkyl polyglucoside (APG) to stabilize the three-phase dispersion between the resin / filler / adsorbent.

[0046] 1. Preparation of PVC resin composition and PVC pipe specimen using the same

[0047] Example 1

[0048] A PVC resin composition was prepared based on 100 parts by weight of a suspension polymerization type PVC resin with a degree of polymerization of 1000, comprising 10 parts by weight of an impact modifier (acrylic), 3 parts by weight of surface-modified nano calcium carbonate (average particle size 40 nm) dry-coated with stearic acid (1.0 wt%), 0.8 parts by weight of a lubricant (butyl / methyl methacrylate), 0.5 parts by weight of a UV blocker, and 0.4 parts by weight of a nonionic surfactant. To this, 9 parts by weight of a microplastic adsorbent (detailed composition: zeolite 4, silica 2, activated carbon 2, Ca-Zn heat stabilizer 5, water glass 1, CMC 0.6, xanthan gum 0.4 parts by weight) was added.

[0049] Afterwards, the prepared raw materials were fed into a high-speed mixer (Super mixer) and dry blended at high speed while raising the temperature to 110°C to induce primary bonding between the surface modifier and the resin, and then cooled to 40°C to produce a compound.

[0050] Then, the manufactured compound was fed into a twin screw extruder with a screw diameter of 50 mm and an L / D ratio of 22. The extrusion temperatures were set to 170°C at the bottom of the hopper (C1), 180°C at C2, 190°C at C3, 195°C at C4, and 200°C at the die, and the screw rotation speed was fixed at 45 rpm. The extruded pipe was passed through a vacuum sizing bath and a cooling bath at 20°C to produce the final specimen.

[0051] Example 2

[0052] [Preparation of composition]

[0053] The same raw materials and composition ratio as in Example 1 were used, except that the content of surface-modified nano calcium carbonate was increased to 5 parts by weight. This was done to confirm the effect of improving mechanical strength with increasing nano filler content.

[0054] Subsequently, the mixing process was carried out using a high-speed mixer in the same manner as in Example 1, involving heating to 110°C and cooling to 40°C. To ensure dispersibility as the nanoparticle content increased, the mixing time was extended by 5 minutes compared to Example 1.

[0055] Then, specimens were prepared using the same twin-screw extruder and temperature profile (170-180-190-195-200℃) as in Example 1. The screw rotation speed was set to 50 rpm considering the torque load.

[0056] Comparative Example 1

[0057] The same composition ratio as in Example 1 was applied, except that 5 parts by weight of ordinary waste stone powder (Micro-CaCO3) with an average particle size of 5㎛ was used instead of nano calcium carbonate as a filler.

[0058] Subsequently, a compound was prepared under the same conditions as in Example 1 (mixing at 110°C, cooling at 40°C). Since microparticles have lower agglomeration compared to nanoparticles, a standard mixing time was applied.

[0059] Then, a PVC pipe was manufactured by molding it using the same extruder and temperature conditions as in Example 1.

[0060] Comparative Example 2

[0061] The same composition ratio as in Example 2 was applied, except that 5 parts by weight of unsurface-treated (unmodified) nano calcium carbonate (average particle size 40 nm) was used as a filler. This was done to confirm the effect of surface modification on dispersibility and physical properties.

[0062] Subsequently, the same mixing process as in Example 2 was performed, but due to the strong cohesive force of the unmodified nanoparticles, some clumping was observed visually in the compound state.

[0063] Then, extrusion was performed under the same temperature conditions as in Example 2, but intermittent flow instability occurred at the die discharge section. The screw speed was maintained at 50 rpm.

[0064] Comparative Example 3

[0065] The same composition ratio as in Example 2 was applied, except that 15 parts by weight of nano calcium carbonate without surface treatment was added as an excess filler. This was done to check for problems (aggregation, deterioration of physical properties) that occur when overfilling occurs.

[0066] Subsequently, when mixing with a high-speed mixer, the viscosity increased due to an excess amount of fine powder, and there were difficulties in manufacturing the compound due to poor dispersion.

[0067] Then, the extrusion torque increased by more than 20% compared to Examples 1 and 2, and a roughness (shark skin) phenomenon occurred on the surface of the formed pipe. The extrusion temperature was maintained at the same level, but the screw speed was lowered to 40 rpm.

[0068] The results of measuring tensile strength (ASTM D638), flexural strength (ASTM D790), impact strength (ASTM D256), microplastic release amount, and surface quality (visual and optical microscope) for specimens prepared in the above examples and comparative examples are as shown in Table 1 below.

[0069] The amount of microplastics released is the result of counting the number of particles larger than 20㎛ after circulating for 1000 hours at a flow rate of 2.0 m / s and a water temperature of 23℃ using a closed-loop water circulation system, and the surface quality is the result of observing the pores, stripes, and roughness of the surface with the naked eye and an optical microscope, and has a value of very good (5) or less than very poor (1).

[0070] division Tensile strength (MPa) Release amount (ea / L) Surface quality Example 1 53 4 5 Example 2 55 3 5 Comparative Example 1 51 12 4 Comparative Example 2 52 18 3 Comparative Example 3 48 25 2

[0071] As can be seen from Table 1 above, Examples 1 and 2 used an appropriate amount (3 to 5 phr) of surface-modified nano-filler to maximize dispersibility within the PVC matrix, thereby significantly improving mechanical properties, and as a result, the amount of microplastics generated by wear was significantly reduced compared to the comparative examples. On the other hand, it was confirmed that Comparative Examples 2 and 3, which lacked surface treatment, actually showed a decrease in properties and an increase in microplastic generation due to aggregation.

[0072] In addition, the amount of microplastics released in Examples 1 and 2 was 3 to 4 ea / L, which is about 65 to 75% lower than that of Comparative Example 1 (12 ea / L). This is because the detachment of surface particles was fundamentally suppressed due to the improved wear resistance and strengthened interfacial bonding strength by the nano filler.

[0073] In addition, Comparative Example 2, which lacked surface treatment, exhibited lower physical properties than Comparative Example 1 due to nano-particle agglomeration, and the amount of microplastics released also increased. In particular, Comparative Example 3, which had an excessive amount added, showed intensified agglomeration and very poor surface quality (decreased gloss, increased roughness), resulting in the highest measured amount of microplastics released. This suggests that it is essential to optimize the content of the nano-filler to the range of 3 to 7 phr and perform surface modification.

[0074] The above description is merely an illustrative explanation of the technical concept of the present invention, and those skilled in the art to which the present invention pertains may make various modifications and variations within the scope of the essential characteristics of the present invention. Accordingly, the embodiments expressed in the present invention are intended to explain, not limit, the technical concept of the present invention, and the scope of rights of the present invention is not limited by such embodiments. The scope of protection of the present invention shall be interpreted by the claims below, and all technical concepts equivalent to or within an equivalent scope shall be interpreted as being included within the scope of rights of the present invention.

Claims

Claim 1 Based on 100 parts by weight of PVC resin, it comprises 2 to 15 parts by weight of impact modifier, 3 to 7 parts by weight of filler, 0.3 to 1 part by weight of lubricant, 0.2 to 1 part by weight of UV blocker, 0.3 to 0.5 parts by weight of nonionic surfactant, and 0.5 to 10 parts by weight of microplastic adsorbent, wherein the filler is surface-modified nano-calcium carbonate (Nano-CaCO3) surface-treated with stearic acid at 0.5 to 2 weight% relative to the weight of nano-calcium carbonate via a dry coating method, the lubricant is a mixture of butyl methacrylate and methyl methacrylate in a weight ratio of 1:1 to 1:2, and the microplastic adsorbent comprises 0.2 to 5 parts by weight of zeolite, 0.5 to 3 parts by weight of silica, and 0.2 to 2 parts by weight of activated carbon powder, based on 100 parts by weight of PVC resin. A microplastic-reducing, high-durability, eco-friendly PVC resin composition comprising an inorganic adsorbent in parts by weight, 1.5 to 6 parts by weight of a heat stabilizer containing a Ca-Zn-based compound, 0.1 to 1 part by weight of water glass which is sodium hydroxide silicate, and a water-soluble anionic polysaccharide, wherein the water-soluble anionic polysaccharide is composed of a mixture of 0.5 to 1.0 parts by weight of carboxymethylcellulose (CMC) and 0.1 to 0.5 parts by weight of xanthan gum per 100 parts by weight of the PVC resin, and is characterized by forming hydrogen-bonded bridges on the surface of the surface-modified nano calcium carbonate particles to secondarily suppress the re-aggregation of the nano calcium carbonate and improve dispersion stability. Claim 2 delete Claim 3 delete Claim 4 A PVC resin composition according to claim 1, characterized in that the heat stabilizer comprises at least one of a Ca-Zn series heat stabilizer, magnesium aluminum hydroxycarbonate, zinc stearate (Zn-St; ZincStearate), and calcium stearate (Ca-St; Calcium Stearate). Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 A PVC resin composition according to claim 1, wherein the surface-modified nano calcium carbonate has an average particle size of 30 to 50 nm. Claim 11 Eco-friendly PVC pipe having a microplastic generation reduction function, characterized by being manufactured from a PVC resin composition of any one of claims 1, 4, and 10.

Citation Information

Patent Citations

  • Formula of corrosion-resistant high-strength PVC board

    CN111574791A

  • Polyvinyl chloride-based resin composition

    JP2005154575A

  • Vinyl chloride-based resin composition and molding of the same

    JP2021147503A

  • Antimicrobial, water and sewage with PVC resin compositions and it has a deodorizing function

    KR101564737B1